The Laws of Plot in The Novel “Ulysses” by James Joyce - Adik Anugrah Sandy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze the plot structure and how the plot laws are applied in the novel "Ulysses" using Kenny's theory. This qualitative research focuses on story plots in order to analyze how story plots are structured in the novel and how the plot laws are applied in the novel. The findings from this study reveal that the storyline is structured like a tree. The plot is developed by the main plot which gives way to four interrelated plots and forms a story with branching plots. The findings indicate that there are two potential meanings derived by the plot structure. First, stories with branching plots increase the tension level of the reader. Second, the sequence of events in the novel shows that the novel "Ulysses" can be considered as a Bildungsroman novel